Mineral status of soil, water, fodder, buffalo’s milk and blood of Meerut district in western Uttar Pradesh: Mineral status of Meerut district of Western Uttar Pradesh - Arya, Vaibhav; Debashis Roy; Ajit Kumar; Ram Kumar Singh; Rajbir Singh; Gulab Chandra; Ahmad Fahim; Nazim Ali; Shalini Vaswani; Vivek Kumar Yadav; Rohit Kumar; Anuj Kumar (Indian Journal of Dairy Science, 2024)
Total 140 feed samples, 120 fodder samples, 105 water samples, 58 milk samples, 51 blood samples and 29 soil samples were collected randomly from all the 12 blocks of Meerut districts. After processing, the samples were analysed for different macro and micro elements by Inductively Coupled Plasma (ICP) instrument (instrument name MY2015CQ05 of Agilent Technologies). Among the feeds, wheat bran was found deficient in copper by 15%. Both copper and zinc content in Mustard oil cake was found marginal. Copper was deficient in bajra fodder, berseem fodder and jowar fodder by 7.5%, 30% and 29.3%, respectively. Sugarcane top, bajra fodder, berseem fodder and jowar fodder were found deficient in zinc by 7.3%, 14.67%, 5% and 2%, respectively. Copper and zinc were also found deficient in blood sample by 15.38% and 1.25%, respectively whereas animal milk samples were deficient in copper by 66.67%. It was found that most of the feed, fodders, blood, milk and soil samples were found deficient in copper and zinc content.